2017
DOI: 10.1111/bph.13797
|View full text |Cite
|
Sign up to set email alerts
|

Propofol induces excessive vasodilation of aortic rings by inhibiting protein kinase Cβ2 and θ in spontaneously hypertensive rats

Abstract: Propofol suppressed increased PKCβ2 and PKCθ activity, which was partly responsible for exaggerated vasodilation in SHR. This suppression results in inhibition of actin polymerization, as well as that of the PKCβ2- but not PKCθ-mediated, Ca sensitization pathway. These data provide a novel explanation for the unwanted side effects of propofol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Hypotension caused by propofol in the process of anesthesia induction is very common and requires the attention of anesthesiologists. Especially for patients with chronic hypertension, the antihypertensive effect of propofol is more significant, which may endanger the life of patients [ 38 ]. Cx37, Cx40, Cx43 and Cx45 are expressed in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotension caused by propofol in the process of anesthesia induction is very common and requires the attention of anesthesiologists. Especially for patients with chronic hypertension, the antihypertensive effect of propofol is more significant, which may endanger the life of patients [ 38 ]. Cx37, Cx40, Cx43 and Cx45 are expressed in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] Previous studies have demonstrated that activation of PKCb 2 and PKCu is enhanced in the aorta of SHRs. 42 This further increases the phosphorylation of the Ca 2+ -sensitization pathway, such as CPI-17-MYPT1-MLC, causing the contraction of vascular smooth muscles. 43 The findings of our study indicated that a high dose of rosuvastatin could decrease the phosphorylation of PKCa in SHRs, suggesting that it might be mediated by the inhibition of PKC.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of Akt and PKCII at these sites increases their kinase activities (55,56). To test their kinase activities, we examined the phosphorylation of their two respective endogenous substrates GSK3 at Ser-9 and myristoylated alanine rich protein kinase C substrate (MARCKS) at Ser-152/156, which elicit many effects of Akt and PKCII, respectively (57)(58)(59). TGF significantly increased the phosphorylation J o u r n a l P r e -p r o o f of GSK3 and MARCKS (Fig.…”
Section: Tgf Increases the Expression Of Dj-1mentioning
confidence: 99%